Investor's Decisions on Financial Reporting: Merger, Aquisition and Consolidation - Marota, Rochman (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study examines the critical role of financial reporting quality in influencing investor decision-making during mergers, acquisitions, and consolidations (M&A). The primary goal is to explore how financial reporting's transparency, accuracy, and relevance affect investor confidence and strategic decision-making in complex corporate transitions. The study aims to provide comprehensive insights into the interplay between financial reporting practices and investor behavior by integrating technical and behavioral perspectives. The study adopts a qualitative systematic literature review approach, drawing on secondary data from peer-reviewed journal articles and books. It evaluates key factors such as transparency, financial literacy, and innovations in reporting practices, including integrated reporting and externality accounting, to understand their impact on investor decision-making. The findings highlight that high-quality financial reporting reduces uncertainty and fosters investor trust. Transparent reporting assists investors in identifying risks and opportunities and bridges the gap between corporate disclosures and investor expectations. Discussions reveal investors' behavioral dynamics, differences between institutional and individual decision-making, and the importance of innovative reporting practices in promoting sustainability and accountability. The study has significant practical implications for companies, regulators, and investors. Companies can adopt innovative reporting strategies to attract and retain investors, while policymakers are encouraged to harmonize global reporting standards to enhance reliability and comparability. For investors, the findings underscore the critical role of financial literacy in interpreting complex financial reports. Future research should explore empirical evidence and investigate the long-term impacts of innovative reporting practices across industries and regions.